GAYA MENGAJAR DOSEN UNTUK MENINGKATKAN HASIL BELAJAR MAHASISWA - Sri Indah Pujiastuti (Fakultas Ilmu Pendidikan Universitas Negeri Jakarta, 2012)
This research aimed at discovering the staff’s lecturing styles at The Early Childhood Education Program, The School of Education, The State University of Jakarta based on four types: formal authority, personal model or demonstrator, fasilitator, dan delegator. The research conducted in September2011 through January 2012, employed descriptive qualitative method with the researcher acting as the instrument. Data were collected by observation, interview, and document study techniques to be validated in triangulation and member check. Data analysis used the procedures of data reduction, data display, and verification/conclusion. The findings indicate that the staff tend to practise facilitator lecturing style oriented on the students and the staff initate various activities involving the students to improve and develop their competence. Based on the research findings, the staff are recommended to improve their professional competence properly.